Síntese e avaliação de sílica tipo M41S contendo cátions CTA em transesterificação catalítica - Fabiano, Demian Patrick (Universidade Federal de São Carlos, 2010)
The investments in the biofuel production have increased a lot in the last years mainly because of smaller damages they cause to the environment in comparison with the derived conventional petroleum fuels. The reaction of biodiesel formation is denominated transesterification and, nowadays that reaction happens in the presence of homogeneous catalyst as the sodium methoxide, sodium hydroxide, (NaOH) or potassium hydroxide (KOH). However, those catalysts create problems such as the possibility of soap formation and they need stages such as the neutralization and washing of the biodiesel. Moreover, the residues of the hydroxides are aggressive to the environment. To eliminate these and other problems, the present work presents a new technology in heterogeneous catalysts with enough basic force to accomplish the transesterification of vegetable oil in tender conditions. For the first time, hybrid catalysts of the type molecular sieves of the family M41S ([CTA]Si-MCM-41, [CTA]Si-MCM-48 and [CTA]Si-MCM-50) were synthesized and used, without modification, in transesterification reactions with monoesters and vegetable oils. The results show that catalysts reach conversions around 96 % in the transesterification of canola oil (1:18) at 79 ºC, however the activity is reduced when the catalyst is reused, due, mainly, to the lixiviation of the CTA+ cation. However, new techniques are being developed in order to increase the catalyst stability.
Keywords: Catálise; Peneiras moleculares; Transesterificação; Biodiesel; M41S; Basic catalysis; Molecular sieves; M41S; Transesterification; ENGENHARIAS::ENGENHARIA QUIMICA